Mortalidade por tuberculose no interior de São Paulo – brasil (2006-2008)/Mortality from tuberculosis in the countryside of São Paulo - Brazil (2006-2008) (Ciência, Cuidado e Saúde, 2015)
This is an epidemiological and descriptive study aiming to characterize the epidemiological profile of deaths due to tuberculosis in the period from 2006 to 2008 of the Regional Health Department III of the State of São Paulo, Brazil. The population was selected through reports of tuberculosis cases recorded in the Tuberculosis Patient Control Registers and death certificates with underlying cause of tuberculosis of the residents of the region covered, registered in the Mortality Information System Department. It was observed 640 reported cases in the Tuberculosis System and 34 deaths in the Information System of Mortality. It was possible to identify 22 deaths when both databases were crossed each other. Thus, there were a total of 45 deaths due to tuberculosis, which occurred mostly in male, with a mean age of 30-59 years and the pulmonary form of the disease. Forty-five percent (45%) of the reported cases occurred outside the primary health care, and the mean interval between notification and death indicated a delayed diagnosis in 77% of the cases. In conclusion, the results showed the importance of data entry reviewing in both information systems, beyond of studies to analyze strategies considered for disease control and also to measure the performance of the primary health care in this context.